Duolingo for Vocabulary Mastery: Empowering Students in the Digital Age of Language Learning - Sabarun; Hesti Widiastuty; Umi Mujiarni (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to evaluate the effectiveness of the Duolingo application in improving vocabulary mastery of 10th grade students at SMKN 2 Palangka Raya in the academic year 2022/2023. The traditional teaching method at SMKN 2 Palangka Raya tends to be monotonous and less interactive, thus, less effective in improving students' vocabulary mastery. This study proposes the integration of the Duolingo application as a learning tool to provide a more interactive and engaging learning experience, as well as to enhance students' vocabulary mastery. A quasi-experimental design is used to compare two classes: X MLPB 2 (conventional method) and X AKL 2 (using Duolingo). Both classes consist of 20 students. Quantitative methods, including normality tests, ANOVA, and Post Hoc, are used for analysis. The results show that the use of Duolingo significantly improves students' vocabulary mastery. The average Post-Test scores increased from 51.857 to 80.714 for class AKL 2, and from 44.706 to 75.147 for class MPLB 2. The integration of technology such as Duolingo has proven to be effective in improving student learning outcomes. Recommendations from this study include increasing the use of technology in language learning curriculum to optimize learning outcomes.